A prospective analysis of injury rates, patterns and causes in Cliff and Splash Diving. Issue 10 (October 2017) - Ernstbrunner, Lukas; Runer, Armin; Siegert, Paul; Ernstbrunner, Matthäus; Becker, Johannes; Freude, Thomas; Resch, Herbert; Moroder, Philipp
Abstract: Introduction: Information about injuries and its differences in Cliff Diving (CD) and Splash Diving (SD) are unknown. It was the aim to analyse (1) injury rates, patterns and causes; (2) differences (in injuries) between both disciplines; and to (3) identify targets for future injury prevention interventions. Methods: From April to November 2013, 81 cliff and 51 splash divers were prospectively surveyed with an encrypted, monthly e-mail-based questionnaire. Results: During a total of 7857 h diving with an average diving height of 13 (±7) m, an overall injury rate of 7.9 injuries/1000 h of sport exposure was reported. Cliff divers most commonly suffered from injuries of the foot and ankle (18%; n = 24) and neck and cervical spine (14%; n = 19). In SD, the lower limb (52%; n = 43) and lower back (23%; n = 19) were most frequently involved. In 79% (n = 49) of the cases, the injury happened while entering the water. Cliff divers were in 52% (n = 15) of the injuries in a feet-first and in 14% (n = 4) in a head-first position. Splash divers were in 45% (n = 9) of the injuries in a back- or buttocks-first position. Most of the injuries were bruises (47%; n = 104) and muscle strains (13%; n = 28). The injury risk during practice was significantly higher than in competition (11.3 vs. 4.5 injuries/1000 h; OR 2.5; p = 0.001). The injury risk of experts (15.4/1000 h exposure) was significantly higher than in professionals (6.3/1000 h exposure; OR 2.4; 95% CI, 3.3–1.9; p < 0.001), although the average diving height was significantly higher in professionals (19 m ± 8 vs. 12 m ± 6; p < 0.001). Significantly more professionals performed dryland training compared to experts (p = 0.006). Conclusion: Most of the injuries are related to the water entry. The entry position plays a key role in injury patterns with pursuant differences comparing CD with SD. Although most of the injuries involved soft-tissue only, severe injuries have been reported. Targets for future injury prevention strategies include protection for the increased impaction at entry; adaption of the diving conditions in practice to those in competition; dryland training courses; and instruction of non-professional divers to teach appropriate diving techniques.